Relationship Between Serum Vitamin D Levels and Anxiety Severity in Elderly Patients at the Internal Medicinie and Psychiatry Clinic of RSUP Prof. dr. I.G.N.G Ngoerah Denpasar - Helen Widiani; Tuty Kuswardhani (MEDICINUS, 2026)
Serum vitamin D plays an important role in both physical and mental health. Decreased serum vitamin D levels in the elderly are often associated with anxiety. This study aims to determine the relationship between serum vitamin D levelsand anxiety severity in elderly patients. A cross-sectional analytical study was conducted and subjects were recruited using consecutive sampling at RSUP Prof. dr. I.G.N.G. Ngoerah. Serum vitamin D levels were measured using the human vitamin D Chemiluminescent Microparticle Immunoassay (CMIA), and anxiety severity were assessed using the Geriatric Anxiety Inventory (GAI). The median age of the participants was 66.5 years (range: 60–83 years). The most common anxiety severity observed was mild (40%) and the most prevalent vitamin D status was insufficient (40%). Statisticalanalysis showed no significant correlation between serum vitamin D levels and anxiety severity (p=0.816). The Spearman correlation test yielded a p-value of 0.214 with a correlation coefficient of -0.125. However, path analysis revealed thatvitamin D indirectly affects anxiety severity through inflammatory bowel syndrome (IBS), with an effect size of -0.06 (p=0.035).